A facile approach to manipulation of osteogenic activity of orthopedic implants by in situ electrically controlled wettability. (10th November 2015) - Chen, Dayong; Gao, Meng; Fu, Yunfeng; Xu, Xiangyang; Hao, Zhao
Graphical abstract: Glycosaminoglycans (GAGs), are the major organic extracellular matrix components, which move around in nanostructured poly(3, 4-ethylenedioxythiophene) (NPEDOT) in respond to the electrical stimulus. The wettability related to the amount of GAGs on NPEDOT surface can be controlled in situ by electrical stimulus, and therefore tune the osteogenic activity of Ti-6Al-4 V orthopedic implants. Highlights: NPEDOT/GAGs are electrochemically constructed on Ti-6Al-4 V orthopedic implants. Electrically controlled wettability is achieved by in situ electrical stimulus. Tuning of osteogenic activity is realized by electrically controlled wettability. Abstract: In this paper, a facile approach to manipulating osteogenic activity of orthopedic implants by in situ electrically controlled wettability was developed. Glycosaminoglycans (GAGs), the major organic extracellular matrix (ECM) components, were electrochemically doped in nanostructured poly(3, 4-ethylenedioxythiophene) (NPEDOT) on Ti-6Al-4 V orthopedic implants. The controlled wettability of NPEDOT/GAGs was achieved by in situ applying electrical stimulus. Moreover, the in situ electrically controlled wettability could be utilized to implement the manipulation of osteogenic activity of orthopedic implants. This facile strategy may open up a new avenue to electrically responsive biomedical applications.